Large‐Scale High‐Speed Jets in Earth's Magnetosheath: Global Hybrid Simulations. Issue 6 (13th June 2022) - Guo, Jin; Lu, San; Lu, Quanming; Lin, Yu; Wang, Xueyi; Ren, Junyi; Hao, Yufei; Huang, Kai; Wang, Rongsheng; Gao, Xinliang
Abstract: High‐speed jets (HSJs) occur frequently in Earth's magnetosheath downstream of the quasiparallel bow shock. They have great impacts on the magnetosheath and the magnetosphere. Using two‐dimensional global hybrid simulations, we investigate the formation and evolution of HSJs with different solar wind conditions. When the quasi‐parallel shock is formed, HSJs begin to appear in the quasi‐parallel magnetosheath. Some elongated HSJs formed at the quasi‐parallel bow shock extend toward the quasi‐perpendicular magnetosheath along with the background magnetosheath flow. As the elongated HSJs moves in the magnetosheath, filamentary structures of the velocity, ion density, and temperature occur in the magnetosheath. The filamentary structures are the traces of HSJs moving in the magnetosheath. Moreover, the Kelvin‐Helmholtz instability can be excited at HSJs, which causes meandering of HSJs. When the interplanetary magnetic field is aligned to the solar wind velocity, the large‐scale HSJs with a parallel (perpendicular) scale size of about 2.5 R E (0.3 R E ) are formed at the magnetosheath where the θ Bn is approaching zero. Then, some HSJs converge, leading to the formation of even larger HSJs with a parallel (perpendicular) scale size of 5 R E (0.6 R E ). Key Points: 2‐D global hybrid simulations are performed to study quasi‐parallel magnetosheath high‐speed jets (HSJs) The elongated HSJs formed at the quasi‐parallel shock extend toward the quasi‐perpendicular magnetosheath, and the traces of HSJs are filamentary structures The solar wind conditions and the convergence of several HSJs lead to the formation of a large‐scale HSJ